2020
DOI: 10.1021/acs.est.9b07592
|View full text |Cite
|
Sign up to set email alerts
|

Rats Sniff Off Toxic Air

Abstract: Breathing air is a fundamental human need, yet its safety, when challenged by various harmful or lethal substances, is often not properly guarded. For example, air toxicity is currently monitored only for single or limited number of known toxicants, thus failing to fully warn against possible hazardous air. Here, we discovered that within minutes living rats emitted distinctive profiles of volatile organic compounds (VOCs) via breath when exposed to various airborne toxicants such as endotoxin, O 3 , ricin, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…5,7 When exposed to substances, the rats were observed to shortly emit distinctive VOC profiles in a recent work. 8 Likewise, when people are infected by SARS-CoV-2, characteristic protein and metabolite changes were observed; and more than 100 lipids were reported to be down-regulated in their blood sera. 9 Here we show that breath-borne ethyl butyrate (C6H12O2) seems to be characteristic of COVID-19 and URTI (SARS-CoV-2 negative) patients (both of them represent respiratory infections) when compared with subjects with LC, HC, and HCW (Table 1).…”
Section: Main Textmentioning
confidence: 99%
“…5,7 When exposed to substances, the rats were observed to shortly emit distinctive VOC profiles in a recent work. 8 Likewise, when people are infected by SARS-CoV-2, characteristic protein and metabolite changes were observed; and more than 100 lipids were reported to be down-regulated in their blood sera. 9 Here we show that breath-borne ethyl butyrate (C6H12O2) seems to be characteristic of COVID-19 and URTI (SARS-CoV-2 negative) patients (both of them represent respiratory infections) when compared with subjects with LC, HC, and HCW (Table 1).…”
Section: Main Textmentioning
confidence: 99%
“…cerevisiae and are thought to be produced mainly through fatty acid decarboxylation and reaction with acetyl coenzyme (acetyl-CoA). , The concentrations of but-1-ene, ethylene, acetylene, ethane, toluene, and ethylbenzene in the yeast inoculum were significantly lower than those in the SC medium, suggesting that these five VOCs were mainly from the background and could be degraded by the yeast cells. In our previous study, ethylene and ethane were also found at higher levels in the indoor air than those in the breath of rats . It has been shown that the S.…”
Section: Resultsmentioning
confidence: 74%
“…This implies that ethyl acetate probably is a common metabolite of yeast in response to external toxic stress. In our previous study, ethyl acetate was also shown to increase in the breath of rats after exposure to ricin . Acetate esters, such as ethyl acetate, isoamyl acetate, and isobutyl acetate, are common flavor metabolites in yeast that have been shown to convert from carboxylic acids by condensation with acetyl-CoA readily and potentially prevent the accumulation of these toxic acids …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, its negative effects increase in haze weather (Wang et al 2015). Bioaerosols also increase the risk of spreading resistance genes (Li et al 2018;Chen et al 2020). In the HVAC system, Yu et al (2019) found that yeast and Penicillium are the main species on the basement walls of residential buildings.…”
Section: Introductionmentioning
confidence: 99%